2017
DOI: 10.1177/0011128717741615
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Police Handling of Juvenile Arrests

Abstract: The overrepresentation of racial and ethnic minority youth in early stages of juvenile justice processing remains a long-standing concern. The current study uses data from the National Incident-Based Reporting System (NIBRS) to examine the effects of race and ethnicity on postarrest handling of juvenile cases by the police. Multilevel analyses controlling for extralegal and contextual factors found that disproportionate minority contact (DMC) was not observed for more severe charges, but Hispanic and minority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…In a systematic review of the literature on race and the punishment of juvenile offenders, Engen et al (2002) found evidence of an impact of race across multiple studies, and in particular, that these effects were stronger in studies that examined earlier decision points in the justice process, such as arrest. Moreover, several studies have also found that these early justice decisions, especially among juveniles, can have a significant impact upon future offending and the receipt of harsher punishments (Claus et al, 2017;Lehmann et al, 2019;Lopes et al, 2012;Sampson & Laub, 1997;Spohn, 2009). These disparities in justice decisions are particularly relevant in relation to the labeling perspective and the application of diversion programs.…”
Section: Juvenile Characteristics and Justice Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of the literature on race and the punishment of juvenile offenders, Engen et al (2002) found evidence of an impact of race across multiple studies, and in particular, that these effects were stronger in studies that examined earlier decision points in the justice process, such as arrest. Moreover, several studies have also found that these early justice decisions, especially among juveniles, can have a significant impact upon future offending and the receipt of harsher punishments (Claus et al, 2017;Lehmann et al, 2019;Lopes et al, 2012;Sampson & Laub, 1997;Spohn, 2009). These disparities in justice decisions are particularly relevant in relation to the labeling perspective and the application of diversion programs.…”
Section: Juvenile Characteristics and Justice Decisionsmentioning
confidence: 99%
“…Within the sociology of punishment literature, there are numerous studies that document the association between community and individual factors and punishment decisions, and more specifically, the decision to divert (Claus et al, 2017; Hamilton et al, 2007; Hayes‐Smith & Hayes‐Smith, 2009; Leiber et al, 2016; Leiber & Stairs, 1999; Rodriguez, 2007; Rodriguez, 2013). There are a number of reasons to anticipate that these effects are of particular concern in the use of civil citation.…”
Section: Relevant Literaturementioning
confidence: 99%
“…What causes this initial disparity in referrals is really the crucial question—but it is an under-researched one (see, e.g. Claus et al, 2018). In part, this is due to the unique methodological challenges involved in assessing the causes of arrest disparities (see Neil & Winship, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Second, focusing on violence neglects other ways that police may serve newer, white gentrifying residents, thus affirming whiteness’ hierarchy in urban space (Lipsitz 2011). For example, police may more quickly respond to white citizens’ calls (Howerton 2006), while also more frequently diverting whites from criminal punishment (Claus, Vidal, and Harmon 2018; Mohamed and Fritsvold 2011). Thus I turn to the broad literature on the racial state, which provides a more thorough framework for analyzing police as a racial project.…”
Section: Police and Planning The Racial Statementioning
confidence: 99%